The effect of globalization on social change: A Field Study in Erbil City - Twana Othman Mohamedamen (QALAAI ZANIST JOURNAL, 2021)
Globalization is a multi-dimensional phenomenal, It has a direct and indirect impact on societies. From this point of view, our research aims to highlight around cultural and social aspects of globalization. In particular demonstration of the impact of globalization on social changes in Kurdish society. This research contained several sections; first section includes two researches of research dimensions. In the first research we focused on problems, significance and the objective of the research and we focused on the second research on definition of globalization and the social changes. The second section devoted on researches that focused on the subject and demonstrated two researches in Kurdish and Arabic languages and also in the third section the connections between globalization and the social and cultural changes were studied, and pointed out thenegative and the positive side of the subject. The fourth section includes the theoretical frame and the field working of the research. And in section five we outlined information obtained in this research. The six and the final section devoted to the findings, initiatives and the recommendations.